Cardiovascular Risk Factors among First Year Medical Students - Dangol, Raj Krishna; Koju, Bibek; Lanjekar, Priya; Pulipati, Chandrashekhar (Journal of Lumbini Medical College, 2017)
Introduction: Detection of cardiovascular risk in young age is important to motivate them to modify life styles and seek health care early to lower the chances of acquiring cardiovascular disease in later age. This study was done to assess cardiovascular risk factors among first year medical students. Methods: A cross-sectional study was conducted throughout September and October 2017 in which all first year medical students from a medical college were assessed for the presence of cardiovascular risk factors. Participants’ demography, family history of illness, anthropometric measurements, and blood reports of lipid profile and fasting glucose were acquired. Data were analyzed with Statistical Package for Social Sciences (SPSS-21). Result: There were 99 participants; 55 males and 44 females. One or more risk factors were present in 87 (87.9%) participants. Moreover, 67.7% (n = 67) participants had more than one risk factors. Low HDL-cholesterol was the most common (n = 55, 55.6%) risk factor followed by elevated triacylglycerol (n = 47, 47.5%) and family history of hypertension (n = 45, 45.5%). There was no significant difference in presence of various risk factors between genders. Conclusion: There was higher prevalence of cardiovascular risk factors among first year medical students. Majority of them had more than one risk factors. Low HDL-cholesterol was the most common risk factor. The risk factors were comparable in males and females.